Yesterday I have been trying to complete this exercise. I have to find: $$ ((map)l)t \simeq \lambda k \lambda x ((k)(t)t_1)....((k)(t)t_n)x $$

where $$l=\lambda k \lambda x ((k)t_1)....((k)t_n)x$$ And $t$ is a generic Lambda term. I tried but without success. Maybe it will be something like that : $$map=(\lambda a \lambda b (\lambda s \lambda d((b(st))d)))$$ Thank you in advance to all will answer


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Browse other questions tagged or ask your own question.